Pengembangan dan Penerapan Sistem Informasi Posyandu untuk Mendukung Akurasi dan Efisiensi Pengelolaan Data Kesehatan - Desriyanti, Desriyanti; Astuti, Arin Yuli; Tsani, Amanda Zulfi Kurnia; Kurniawan, Andyra Aldy; Anwari, Ahmad Choirul; Nasrullah, Choirul Amri; Saputro, Yayan Bekti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Integrated Service Post (Posyandu) is a community-based health program that aims to facilitate access to health services, especially for babies, toddlers and the elderly. Posyandu Melati in Pudak District, Ponorogo Regency, regularly holds activities such as weighing, immunizations and giving vitamins. However, manual recording carried out by cadres often causes problems, such as recording errors and difficulties in managing data efficiently. This service aims to develop a web-based Posyandu information system using the Laravel framework with the Model View Controller (MVC) concept. This system is designed to facilitate monitoring of child growth and development, immunization and health screening, as well as increasing the efficiency of Posyandu data management. Key features include health data management, immunization monitoring, and health history tracking. The results show that this system is able to help cadres and admins manage health data more accurately, quickly and organizedly, as well as speeding up the delivery of information to the public. It is hoped that this system can improve the quality and effectiveness of health services at the village level and support overall improvement in community welfare.